PENGARUH PROFITABILTAS, LIKUIDITAS DAN GOOD CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL - Wati, Linda; Hariani, Lilik Sri; Yogivaria, Doni Wirshandono (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2019)
This study aims to examine and determine the effect both simultaneously and partially between return on assets, return on equity, current ratio, quick ratio, board of directors, independent commissioners on the capital structure of automotive companies listed on the Indonesia Stock Exchange in the period 2013-2017. The data of this study were obtained from the Investment Gallery of Kanjuruhan University Malang and the Indonesia Stock Exchange Site, www.idx.co.id. The sampling technique uses purposive sampling which is based on certain criteria in order to obtain 6 companies that are used as research samples. The analysis technique used is multiple regression analysis. The results showed that simultaneous return on assets, return on equity, current ratio, quick ratio, board of directors, independent commissioners influence the company's capital structure. Partially return on assets, return on equity, current ratio, quick ratio, board of directors, independent commissioners negatively affect the company's capital structure